(3YLGdI GdQGcH hbHS GdPGgHs - (3Cejf Hf eMeO Hf SjO CMeO GdOjeGfjs
(3ChdgG (B:s
(3hHYO adeG QCjJ CHfGA GdReGf , hdGSjeG ai gPG GdChGf , ai cd hGO ef cJGH Gddg jgjehf , hjRfhf Hg cd GdXfhf MedJfi GdMejI GdCHjI , hgeI ZjQ CMhPjI hSejJg s
(3BNQgG (B:s
(3hbhdg JYGdi (B: " (3hEPG GdCQV eOJ(B" (3aeO GdCQV ERGdI LHGdgG MJi dGjHbi ajgG EQJaGY hdG GfNaGV s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI bOjeIs
(3HYV GdYfGhjf HGdMeQI s
(3hahGUdgG HGdMeQI s
(3hCWQGagG GdYdhjI eJbUaI aVGYJ HYV GdcdeGJ hGdSWhQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs